2012
DOI: 10.1111/j.1445-2197.2011.05969.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of intraductal breast papilloma diagnosed on core biopsy

Abstract: In our study, 19% of patients with a benign papillary lesion diagnosed on core biopsy were found to have atypical ductal hyperplasia or malignancy following surgery. In view of this, together with the absence of reliable predictive factors for malignancy, we recommend surgical excision of all papillary lesions diagnosed on core biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Seven studies [7,22,36,38,39,42,44] are comparable to our study considering the homogeneity of series reported (US 14G NCB). These studies report a range of underestimation rate between 15 and 47 %, and our value of underestimation rate (47.8 %) results to be very close to superior limit of this range.…”
Section: Papillary Lesions With Epithelial Atypiasupporting
confidence: 89%
“…Seven studies [7,22,36,38,39,42,44] are comparable to our study considering the homogeneity of series reported (US 14G NCB). These studies report a range of underestimation rate between 15 and 47 %, and our value of underestimation rate (47.8 %) results to be very close to superior limit of this range.…”
Section: Papillary Lesions With Epithelial Atypiasupporting
confidence: 89%
“…showed that areas of atypia or carcinoma may be overlooked in the limited needle biopsy samples because of potential histologic heterogeneity within a papillary lesion . Several studies have recommended that all cases of IDP identified on core needle biopsy should be excised because a proportion of IDP without atypia will be upgraded to atypia or carcinoma on excisional specimens . From the present study, we learned that even for patients with IDP without atypia diagnosed on needle biopsy, further excisional biopsy should be considered if the possibility of coexisting malignancy cannot be ruled out from clinical and imaging findings.…”
Section: Discussionmentioning
confidence: 97%
“…This task is all the more challenging for lesions like papillomas, which typically arise in large ducts and are best evaluated in one contiguous and inclusive section. In 2012, Lu et al 22 reported that the average size of the lesions that were biopsied with a 14-gauge needle and upgraded after excision was only 13 mm, suggesting that even small lesions may not be adequately and accurately sampled by core biopsy. Given this reported underestimation rate for atypia or malignancy, our institution routinely offers surgical excision for most patients with a papillary lesion diagnosed on core biopsy, regardless of core biopsy size, histologic features, or radiographic characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…[23][24][25][26][27][28][29] The preceding CNB studies that quote high excision upgrade rates largely included patients who underwent first-generation CNB procedures with stereotactic mammography or ultrasound for localization using an automated biopsy gun equipped with a 14-gauge or smaller needle. 10,15,22 An 8-to 12-gauge vacuum-assisted device allows for significantly greater sampling of a lesion, potentially improving the predictive value of a biopsy. Berg et al 20 showed that an 11-gauge device typically yields a fivefold greater volume of material per core compared with a 14-gauge automated biopsy gun.…”
Section: Discussionmentioning
confidence: 99%